Analysis Of Raw Material Inventory At Sultan 888 Coffee Powder In Simpang Nangka Village Rejang Lebong District - Putri Kurnia; Yun Fitriano; Ramadan Subhi (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Raw materials are one of the determining factors in the smooth production process.The obstruction of the production process will affect the output produced and reduce consumer confidence in the company. For this reason, it is necessary to control the inventory of raw materials using Economic Order Quantity (EOQ) method. This study aims to determine how business activities place orders, determine the optimal amount of inventory in placing orders. This analysis is carried out using the Economic Order Quantity, Reorder Point, Safety Stock methods. EOQ aims to determine the amount of raw materials ordered and minimize the total cost of ordering and storage. Reorder point aims to find out when to order back appropriately, and Safety Stock aims to provide security if the order period is not appropriate. Data collection methods using documentation and interviews. The results of research and discussion using EOQ method obtained more effective results. This can be seen from the comparison of company policy with EOQ method. During this time the company made an average purchase of 277.5 kg with a frequency of 24 orders a year. The total inventory cost is Rp 3,804,166. Meanwhile, when using EOQ method, the average purchase amount is 137 kg with an order frequency of 5 times a year. The total cost of inventory is Rp 1,482,639 a year. The safety stock required by the company is 18.5 kg and the company must place a reorder point when the inventory has reached 42.28 kg. From these results, it can be compared if the system currently running in the company incurs higher costs compared to using EOQ method.